The new political economy of Russia - Berglöf, Erik (MIT Press, 2003)
An analysis of the challenges facing Russia's economy ten years after the transition, based on recent research and data. Can Russia's recent burst of economic growth be sustained? Taking a comprehensive look at the economic and political regime shift from Yeltsin to Putin, this book explores the key challenges facing the Russian economy: to narrow the productivity gap between Russian and Western firms and industries; to attract more domestic and foreign investment; and, underlying these goals, to implement the judicial, administrative, social, and banking reforms necessary to future growth. Written by a team of researchers from the Center for Economic and Financial Research--a Moscow-based independent think tank--the book draws on a wealth of new research and data. The authors emphasize the need to strengthen the protection of property rights, restructure the banking sector, and reduce government officials' powers to intervene arbitrarily in private businesses. They also stress the importance of enhancing human capital--through educational reform and by reducing barriers to citizens' geographical and sectoral mobility. Considering political institutions, the authors examine the promise and risks of the centralization of power around President Putin. Finally, they discuss the likely impact of Russia's greater integration into the world economy, notably through its potential membership in the World Trade Organization.